2017
DOI: 10.1016/j.neuron.2016.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Transient Opening of the Mitochondrial Permeability Transition Pore Induces Microdomain Calcium Transients in Astrocyte Processes

Abstract: Summary Astrocytes extend highly branched processes that form functionally isolated microdomains, facilitating local homeostasis by redistributing ions, removing neurotransmitters and releasing factors to influence blood flow and neuronal activity. Microdomains exhibit spontaneous increases in calcium (Ca2+), but the mechanisms and functional significance of this localized signaling are unknown. By developing conditional, membrane anchored GCaMP3 mice, we found that microdomain activity that occurs in the abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
455
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(503 citation statements)
references
References 54 publications
22
455
2
2
Order By: Relevance
“…Astrocyte function is compartmentalized, and little is known about the effect disease conditions have on the homeostasis and function of distinct astrocyte compartments (Agarwal et al, ; Dunn et al, ; Lind et al, ; Oheim, Schmidt, & Hirrlinger, ; Rungta et al, ; Shigetomi et al, ). Using saline and Ang II‐infused GLAST‐CreERT2; R26‐lsl‐GCaMP3 mice, where compartmentalized Ca 2+ activity can be readily assessed, we show increased spontaneous astrocyte Ca 2+ events in MD of hypertensive mice.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocyte function is compartmentalized, and little is known about the effect disease conditions have on the homeostasis and function of distinct astrocyte compartments (Agarwal et al, ; Dunn et al, ; Lind et al, ; Oheim, Schmidt, & Hirrlinger, ; Rungta et al, ; Shigetomi et al, ). Using saline and Ang II‐infused GLAST‐CreERT2; R26‐lsl‐GCaMP3 mice, where compartmentalized Ca 2+ activity can be readily assessed, we show increased spontaneous astrocyte Ca 2+ events in MD of hypertensive mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, Pr(Mitochondria) was significantly lower than Pr(HW) in small processes and larger than Pr(HW) in thicker processes (the effect of HW: F (19,114) = 16.65, p < .0001; Pr(Mitochondria) vs Pr(HW): F (1,6) = 1.384, p = .28; interaction: F (19,114) = 8.422, p < .0001; n = 7, two‐way RM ANOVA, post hoc Bonferroni's multiple comparison; Supporting Information Figure S2C). This finding suggested that although mitochondria may contribute to astrocytic Ca 2+ activity (Agarwal et al, ), this does not explain the morphology‐dependent Ca 2+ activity observed here.…”
Section: Resultsmentioning
confidence: 53%
“…A recent report suggests that mitochondrial permeability transition pore may transiently open and induces microdomain Ca 2+ transients in astrocytic processes (Agarwal et al, ). If this is the case, Ca 2+ events initiation points should co‐localize with mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…Other functional significances of IP 3 R2‐independent Ca 2+ nanodomains around the ER require further clarification. Thus, in addition to extracellular and mitochondrial sources of Ca 2+ that have been clearly indicated as IP 3 R2‐independent Ca 2+ signaling mechanism (Agarwal et al, ; Srinivasan et al, ), IP 3 R2‐independent Ca 2+ release from the ER may contribute to Ca 2+ signaling in IP 3 R2‐KO astrocytes.…”
Section: Discussionmentioning
confidence: 99%